Association of the intraoperative peripheral perfusion index with postoperative morbidity and mortality in acute surgical patients: a retrospective observational multicentre cohort study. (September 2021) - Agerskov, Marianne; Thusholdt, Anna N.W.; Holm-Sørensen, Henrik; Wiberg, Sebastian; Meyhoff, Christian S.; Højlund, Jakob; Secher, Niels H.; Foss, Nicolai B.
Abstract: Background: We hypothesised that in acute high-risk surgical patients, a lower intraoperative peripheral perfusion index (PPI) would indicate a higher risk of postoperative complications and mortality. Methods: This retrospective observational study included 1338 acute high-risk surgical patients from November 2017 until October 2018 at two University Hospitals in Denmark. Intraoperative PPI was the primary exposure variable and the primary outcome was severe postoperative complications defined as a Clavien–Dindo Class ≥III or death, within 30 days. Results: intraoperative PPI was associated with severe postoperative complications or death: odds ratio (OR) 1.12 (95% confidence interval [CI] 1.05–1.19; P <0.001), with an association of intraoperative mean PPI ≤0.5 and PPI ≤1.5 with the primary outcome: OR 1.79 (95% CI 1.09–2.91; P =0.02) and OR 1.65 (95% CI 1.20–2.27; P =0.002), respectively. Each 15-min increase in intraoperative time spend with low PPI was associated with the primary outcome (per 15 min with PPI ≤0.5: OR 1.11 (95% CI 1.05–1.17; P <0.001) and with PPI ≤1.5: OR 1.06 (95% CI 1.02–1.09; P =0.002)). Thirty-day mortality in patients with PPI ≤0.5 was 19% vs 10% for PPI >0.5, P =0.003. If PPI was ≤1.5, 30-day mortality was 16% vs 8% in patients with a PPI >1.5 ( P <0.001). In contrast, intraoperative mean MAP ≤65 mm Hg was not significantly associated with severe postoperative complications or death (OR 1.21 [95% CI 0.92–1.58; P =0.2]). Conclusions: Low intraoperative PPI was associated with severe postoperative complications or death in acute high-risk surgical patients. To guide intraoperative haemodynamic management, the PPI should be further investigated.